Measurement of haem and total iron in fish, shrimp and prawn using ICP-MS: Implications for dietary iron intake calculations. (15th June 2016) - Wheal, Matthew S.; DeCourcy-Ireland, Emma; Bogard, Jessica R.; Thilsted, Shakuntala H.; Stangoulis, James C.R.
Highlights: Total Fe, haem Fe and non-haem Fe were measured by ICP-MS in 25 aquatic food species from Bangladesh. Average total Fe ranged from 0.55 to 14.43 mg/100 g fresh weight. Haem Fe represented <20% to >90% of total Fe depending on species and decreased as total Fe increased. Repeated 60 min extractions of tissue in 80% acetone yielded additional haem Fe. Previous haem Fe contributions to dietary intake from fish are likely to have been underestimated. Abstract: Twenty-five species of fish, shrimp and prawn from local markets in Bangladesh were analysed for concentrations of total Fe, haem Fe and non-haem Fe by ICP-MS. Total Fe and non-haem Fe concentrations were measured in nitric acid-digested samples and haem Fe was extracted using acidified 80% acetone for 60 min. Total Fe concentrations ranged from 0.55–14.43 mg/100 g FW, and haem Fe% ranged from 18%–93% of total Fe. Repeat extractions with 80% acetone recovered additional haem Fe, suggesting that previous measurement by this technique may have underestimated haem Fe content. Calculation of Fe balance (summing Fe in acetone extracts and Fe in the residue after haem Fe extraction) was not significantly different from total Fe, indicating the two processes recovered the different forms of Fe with similar effectiveness.